A framework for load shedding and demand response in DC microgrid using multi agent system - Diana Rwegasira; Imed Ben Dhaou; Anastasia Anagnostou; Aron Kondoro; Naiman Shililiandumi; Amleset Kelati; Simon J.E. Taylor; Nerey Mvungi; Hannu Tenhunen (My University, 2022)
This paper presents a framework of load shedding experiment for a DC Microgrid using Multi-Agent System (MAS). The microgrid uses solar panels as source of energy to serve a community without access to electricity. The generated framework includes modelling of solar panels, battery storage and loads for effective control and better operation. The loads are classified as critical and non-critical loads. The agents are designed in a decentralized manner which include solar agent, storage agent and load agent. The load shedding experiment of the framework is mapped with the manual operation done at Kisiju village, Pwani, Tanzania. The results of the experiment focus on using accurate solar and PV panels which provide: (i) the multi agent system that runs in the DC microgrid, (ii) the controlling and monitoring of power to be used for critical and non-critical loads and (ii) the management power in the production process through selling extra power from an individual load to the storage.
2017 21st Conference of Open Innovations Association (FRUCT 2017)